Higher Charlson Comorbidity Index scores do not influence Functional Independence Measure score gains in older rehabilitation patients. (12th September 2016) - Bernard, Sarah; Inderjeeth, Charles; Raymond, Warren
Abstract : Aim: To assess the effect of age‐adjusted Charlson Comorbidity Index (CCI) score on Functional Independence Measure (FIM) score gain in older rehabilitation patients. Methods: This prospective cohort study observed 306 older rehabilitation patients admitted to a secondary hospital between February and April 2015. Groups were compared using CCI score cut‐offs of ≤4, 5–6 and ≥ 7. Results: Complete FIM data were available for 280 patients. The mean age‐adjusted CCI score was 5.59 ± 1.96. An age‐adjusted CCI score ≤4 correlated with higher FIM scores at admission P = 0.015, and discharge P = 0.002, but not with a greater gain in FIM score P = 0.067 . There were no significant between‐group differences in mortality, hospital transfers or length of stay . Conclusion: The Charlson age‐comorbidity index was not a prognostic marker for FIM gain. Age and comorbidity alone are not barriers to the rehabilitation of older patients.